Performance Optimisation of Hybrid Renewable Systems for Remote Off-Grid Electrification - Kalyankolo Umaru; Kaaya Salim; Salaama Asikuru; Noah Ochima; Pison Mutaburura; Yudaya Nansukusa; Nafuna Ritah (Lamintang Education and Training (LET) Centre, 2026)
This research focuses on modelling, simulation and optimization of a HRES for off grid electrification in remote areas of Uganda using solar and wind as the renewable sources, targeting a community of 100 households and 10 medical centers in Rigbo Sub-County, Arua District. Using HOMER Pro software, five configurations were evaluated: solar only, solar and wind, solar with generator, wind with generator, and a combination of solar and wind with generator. Costs, electrical performance and environmental impact of the configurations were compared. Load profiles were developed by estimating a daily consumption of households and medical centers, scaled to total annual load of 189,500-189,581kWh. Results indicate that hybrid systems incorporating a generator, particularly the configuration of solar, wind and generator, outperforms others with the lowest total NPC and the lowest LCOE and no unmet load, while maintaining high renewable fraction and manageable CO2 emission. Future studies should focus on validating these simulation results with empirical data from actual pilot deployments in remote Ugandan villages to account for real-world weather unpredictability. Investigating more dynamic and diverse energy demand models would also provide a deeper understanding of consumption patterns beyond uniform assumptions. Exploring the integration of advanced energy storage technologies and smart grid management could offer ways to further reduce reliance on diesel generators while maintaining system reliability.